2007
DOI: 10.1210/en.2006-1086
|View full text |Cite
|
Sign up to set email alerts
|

The Low-Density Lipoprotein Class A Module of the Relaxin Receptor (Leucine-Rich Repeat Containing G-Protein Coupled Receptor 7): Its Role in Signaling and Trafficking to the Cell Membrane

Abstract: The relaxin receptor (LGR7, relaxin family peptide receptor 1) is a member of the leucine-rich repeat containing G protein-coupled receptors subgroup C. This and the LGR8 (relaxin family peptide receptor 2) receptor are unique in having a low-density lipoprotein class A (LDL-A) module at their N termini. This study was designed to show the role of the LDL-A in LGR7 expression and function. Point mutants for the conserved cysteines (Cys(47) and Cys(53)) and for calcium binding asparagine (Asp(58)), a mutant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
81
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 44 publications
15
81
0
2
Order By: Relevance
“…In the present study, the protein encoded by RXFP1 was translated into three protein species with apparent molecular masses of 75, 91 and 95 kDa in the testis during development. Taken with previous findings (Kern et al 2007), specific bands of both 91 and 95 kDa detected in the boar testis are likely to be glycosylated forms of the RXFP1 receptor, whereas the 75 kDa band may represent a non-glycosylated form, although it is somewhat smaller in size than the non-glycosylated human RXFP1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, the protein encoded by RXFP1 was translated into three protein species with apparent molecular masses of 75, 91 and 95 kDa in the testis during development. Taken with previous findings (Kern et al 2007), specific bands of both 91 and 95 kDa detected in the boar testis are likely to be glycosylated forms of the RXFP1 receptor, whereas the 75 kDa band may represent a non-glycosylated form, although it is somewhat smaller in size than the non-glycosylated human RXFP1.…”
Section: Discussionsupporting
confidence: 88%
“…Members of this family of receptors have N-glycosylation sites in the ectodomains and act through causing cAMP production (Hsu et al 2002, Yan et al 2008b. Expression analysis and glycosidase treatment have shown that human RXFP1 is expressed as two molecular masses of 80 and 95 kDa in human embryonic kidney cells (HEK293 cells) transfected with the full-length RXFP1, and that while the 95 kDa band represents the glycosylated form of the RXFP1 receptor, the 80 kDa band represents the non-glycosylated form (Kern et al 2007). In the present study, the protein encoded by RXFP1 was translated into three protein species with apparent molecular masses of 75, 91 and 95 kDa in the testis during development.…”
Section: Discussionmentioning
confidence: 99%
“…6C). A previous study by Kern et al (25) involving immunoprecipitation and Western blotting for HA-tagged RXFP1 shows the presence of two distinct immunoprecipitated bands, at 95 kDa and 80 kDa, the larger of which corresponds to the mature form of the receptor (25). In our hands, FLAG-tagged RXFP1 migrates as a broad single band at 80 -90 kDa, and the mature and immature forms are unable to be distinguished (52).…”
Section: Resultssupporting
confidence: 40%
“…In addition to the LRR region, the N-terminal LDLa module is essential for signaling ( Fig. 1) but has no role in ligand binding Hopkins et al, 2007;Kern et al, 2007). The LDLa module likely interacts with other receptor domains (potentially the ECLs and TM domains) in a manner analogous to a tethered ligand (Fig.…”
Section: B Structural Features Of Relaxin Family Peptide Receptorsmentioning
confidence: 99%